Molecular Identification of Cryptosporidium spp., Enterocytozoonbieneusi, and Giardiaduodenalis in Captive Pet Birds in Henan Province, Central China. (31st January 2021) - Dong, Haiju; Cheng, Ru; Li, Xinmiao; Li, Junqiang; Chen, Yuancai; Ban, Chaoping; Zhang, Xiangqian; Liu, Fang; Zhang, Longxian
Abstract: Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis are common enteric pathogens that are capable of infecting humans and animals. Total of 1, 005 fecal samples from captive pet birds were collected from seven locations in Henan Province, China. The results demonstrated that 9.9% (99/1, 005) of the captive birds were infected with one of these three pathogens. Enterocytozoon bieneusi was the most prevalent species among the birds (45/1, 005, 4.5%) followed by G . duodenalis (33/1, 005, 3.3%) and Cryptosporidium spp. (21/1, 005, 2.1%). Five Cryptosporidium species were identified, namely, C . baileyi (10), C . galli (5), C . meleagridis (4), C . andersoni (1), and C . parvum (1). Two known E . bieneusi genotypes were identified: Peru 6 (44) was identified in pigeons (34) and European turtle doves (10); whereas, the genotype PtEb I (1) was only identified in a pigeon. Only G . duodenalis assemblage E (33) was identified in some pet birds. To the best of our knowledge, this study is the first to undertake the molecular identification of G . duodenalis in birds in China. The identification of potentially zoonotic species/genotypes of the pathogens suggests that exposure to the excreta of these birds, either directly or via food and water, may pose a threat to human health.